A Survey of Elementary School Teachers' Self-Reflection Skills: Uncovering the Role of Reflection in Improving Learning Quality - Rokayah, Rokayah; Rahayu, Ai Hayati (Universitas Pendidikan Indonesia, 2024)
Teachers' reflective ability is a critical factor in improving the quality of learning in elementary schools. Reflection enables teachers to critically evaluate their teaching practices, identify strengths and weaknesses, and develop more effective strategies to address students' needs. This study aims to assess the level of self-reflective ability among elementary school teachers using a survey method and to explore how reflection contributes to enhancing teaching quality. The survey included 316 elementary school teachers from various regions in Indonesia and was conducted online using a teacher self-reflection questionnaire. The results revealed that teachers' reflective abilities were generally categorized as good. While most teachers acknowledge the importance of reflection, challenges remain in implementing deep and structured reflective practices. Key barriers include high workloads, limited time, and insufficient professional support. Furthermore, a lack of understanding of the reflective process and the absence of supportive tools to guide teachers through this process hinder the effective application of reflection.